Heavy Metal Phytoremediation: Plant Hyperaccumulators and Clean Strategies for the Environment - Nurmustaqimah; Jamilatun, Siti; Rahayu, Aster; Hakika, Dhias Cahya; Muthadin , Akhmad Sabilal; Taufiqurahman , Muhamad Akmal (Indonesian Journal of Chemical Engineering, 2024)
Increasing urbanization and industrialization have led to serious heavy metal pollution problems, detrimental to the environment and human health. Phytoremediation, which utilizes hyperaccumulator plants such as Indian mustard and water hyacinth, presents an efficient and sustainable alternative. Despite having the advantages of low cost and utilization of renewable natural resources, phytoremediation also carries risks, such as contamination of consumable plant parts and limited efficiency. Therefore, selecting the right hyperaccumulator plants and having an in-depth understanding of phytoremediation mechanisms are the keys to increasing their success. Phytoremediation mechanisms, such as phytoextraction, hemofiltration, and phytostabilization, can be implemented by considering environmental conditions and contaminants. Factors such as the nature of the medium, root zone, and environmental conditions play a crucial role in determining the effectiveness of phytoremediation. Although challenges still exist, phytoremediation remains a promising approach to treating heavy metal pollution in an economical and environmentally friendly manner.